2007
DOI: 10.1136/bmj.39420.533461.25
|View full text |Cite
|
Sign up to set email alerts
|

Enduring beliefs about effects of gassing in war: qualitative study

Abstract: Objectives To discover the content of enduring beliefs held by first world war veterans about their experience of having been gassed. Design Collection and thematic analysis of written and reported statements from a sample of veterans about gassing. Subjects 103 veterans with a war pension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 15 publications
0
19
0
Order By: Relevance
“…Physical effects of gas poisoning are described as so severe and debilitating that they are associated with a limited capacity to work (15). Physical disability interferes a lot with participants’ ability to function, especially as they lose their ability progressively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Physical effects of gas poisoning are described as so severe and debilitating that they are associated with a limited capacity to work (15). Physical disability interferes a lot with participants’ ability to function, especially as they lose their ability progressively.…”
Section: Discussionmentioning
confidence: 99%
“…Most survivors are also suffering from significant psychological disorders including a progressive sense of alienation, depression, loss of family unity, posttraumatic stress disorder and anxiety (14). Chemical weapons victims suffer from irreversible and deteriorating health status (15). The results of recent interpretive sociological studies of chronic illness suggest the need for a multidimensional view of chronic illness impact on everyday life (16).…”
Section: Introductionmentioning
confidence: 99%
“…Mental health effects are also pronounced. [1116] Delayed effects, e.g., neuropsychiatric symptoms, become obvious only in the longer term. [11] The majority of survivors of SM exposure suffer from severe, long-lasting respiratory conditions, primarily chronic bronchitis, chronic obstructive pulmonary disease (COPD), bronchiolitis obliterans, emphysema, pulmonary fibrosis, bronchiectasis, tracheal and/or bronchial deformities, and recurrent pneumonia.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the experience of CWAs and fear of renewed exposure to CWAs implies chronic poor health status and post-traumatic stress disorder (PTSD). [16, 22, 23] A recent study reports that SM effects on the respiratory system in particular are closely associated with psychiatric disorders. [22] A study on Iranian male war veterans revealed that SM victims with ophthalmological complications had lower health-related quality of life (HRQOL) compared to a control group.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the chemical agent, the "active principle" itself, is extremely toxic, but then, under real use conditions, chemical weapons are only 5% fatal on battlefields due to the complications in their dissemination and dispersal (for gaseous chlorine in World War I and for blistering sulfurÀmustard agents in IranÀIraq war, a mortality of 2% and 4%, respectively, were recorded) (Bismuth et al 2004;Jones, Palmer, and Wessely 2007). Nevertheless, toxic warfare agents inflict high numbers of injuries, causing a considerable logistical burden to the emergency sanitary system and a heavy psychological impact on the target population (Koenig et al 2008;Zilker 2005).…”
Section: Wrong Commonplacesmentioning
confidence: 99%